Persepsi Siswa tentang Pembelajaran Diferensiasi pada Mata Pelajaran Informatika Kelas VII MTsN 7 Agam - Annisa Fitri; Zulfani Sesmiarni (MASALIQ, 2026)
Differentiated learning is one of the approaches within the Kurikulum Merdeka designed to accommodate the diversity of students’ learning needs, interests, abilities, and characteristics. However, studies examining students’ perceptions of the implementation of differentiated learning in Informatics remain limited. This study aims to analyze the perceptions of seventh-grade students at MTsN 7 Agam regarding differentiated learning in Informatics. The study employed a quantitative approach using a descriptive method. The study population comprised 241 seventh-grade students, while a sample of 150 students was selected through proportionate random sampling. Data were collected using a questionnaire consisting of 20 statement items covering the indicators of content differentiation, process differentiation, product differentiation, learning motivation, and understanding of the material. The data were analyzed using descriptive statistics in the form of mean scores and percentages. The instrument testing results showed an Aiken’s V validity value of 0.75 and a Cronbach’s alpha reliability coefficient of 0.816, and all statement items were declared valid. The results showed that students’ perceptions of differentiated learning were in the very good category, with a percentage of 85.85%. The mean score for each indicator was 4.42 for content differentiation, 4.02 for process differentiation, 4.29 for product differentiation, 4.37 for learning motivation, and 4.37 for understanding of the material. These findings confirm that students have highly positive perceptions of the implementation of differentiated learning in Informatics. This study provides practical implications for teachers in designing more adaptive and student-centered learning to accommodate diverse learning needs and improve students’ motivation and understanding.